PEMBELAJARAN MENULIS PUISI PADA SISWA KELAS X SMA NEGERI 1 SEGEDONG KABUPATEN MEMPAWAH - Khatimah, Khusnul; Syambasril, Syambasril; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by the lack of interest of students to the literary works, one of whom wrote poetry. So the problem that arises is how the learning to write poetry on the students of class X SMA Negeri 1 Segedong Mempawah lesson year 2017/2018. This research method is descriptive. Form of research used qualitative. Sources of data in this study are Indonesian teachers and students of class X SMA Negeri 1 Segedong. Data collection techniques use observation and test techniques. Data analysis technique using qualitative descriptive model. The results or conclusions of this study are: 1) Implementation of learning in the form of preliminary activities undertaken by the teacher has been implemented all well; 2) Implementation of learning in the form of core activities that are divided in the mastery of the material, the application of learning strategies, learning to write poetry, process assessment and learning outcomes, and the use of language; 3) Implementation of learning in the form of closing activities is the teacher with students concluded the material has been studied. The teacher asks a message that can be taken from the material, the teacher also conducts an assessment of the learning activities; 4) Assessment of the final results using the assessment rubric. The technique of writing poetry writing skills using product assessment techniques (work).Keywords: Learning, Writing, Poetry